Environmental impacts of III–V/silicon photovoltaics: life cycle assessment and guidance for sustainable manufacturing. Issue 11 (6th October 2020) - Blanco, Carlos F.; Cucurachi, Stefano; Dimroth, Frank; Guinée, Jeroen B.; Peijnenburg, Willie J. G. M.; Vijver, Martina G.
Abstract : By requiring less materials, multijunction III–V/silicon photovoltaic cells may further reduce the life cycle environmental impacts of solar PV. Abstract : Multijunction III–V/silicon photovoltaic cells (III–V/Si), which have achieved record conversion efficiencies, are now looking as a promising option to replace conventional silicon cells in future PV markets. As efforts to increase efficiency and reduce cost are gaining important traction, it is of equal importance to understand whether the manufacturing methods and materials used in these cells introduce undesired environmental trade-offs. We investigate this for two state-of-the-art III–V/Si cell design concepts using life cycle assessment. Considering that the proposed III–V/Si technologies are still at an early research and design stage, we use probabilistic methods to account for uncertainties in the extrapolation from lab-based data to more industrially relevant processes. Our study shows that even at this early stage and in light of potential uncertainties, the III–V/Si PV systems are well positioned to outperform the incumbent silicon PV systems in terms of life-cycle environmental impacts. We also identify key elements for more sustainable choices in the III–V/Si design and manufacturing methods, including the prioritization of energy efficiency measures in the metalorganic vapour phase epitaxy (MOVPE) process and a reduction in the consumption of indium trichloride in spray pyrolysis.